PENGARUH MODAL INTELEKTUAL DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. JAYA BRAVO - Dika Wahyudin; M. Kausar Maulana (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
The research objective was to determine the effect of intellectual capital and leadership on the performance of employees at PT. Jaya Bravo. In this study used 30 sample respondents. Methods of data analysis using simultaneous linear regression analysis techniques and partial linear regression. The results of the study concluded that there is a significant influence of intellectual capital and leadership on the performance of employees of PT. Jaya bravo, both simultaneous and partial.